SCHOOL CASH DEVELOPMENT AT MTS AL MANSUR: INTEGRATION OF ESP32, TCS3200 COLOR SENSOR, AND FIREBASE-BASED REAL-TIME USER INTERFACE - Bagas Irvan Maulana; Ardelia Astriany Rizky (INFOKOM (Informatika & Komputer), 2025)
This research aims to design and build an Internet of Things (IoT)-based cash system using an microcontroller integrated with the Firebase Realtime Database. The system is designed to automatically record student deposit transactions using the TCS3200 color sensor, then send the data to Firebase using the ESP32 module. The stored data can be accessed by students in real-time through the Firebase interface. The system workflow begins with attendance using the keypad, followed by students inserting money into the cash register. The TCS3200 color sensor detects the nominal amount of money based on the corresponding color, then the servo motor functions to drop the money into the cash box. The sensor detection accuracy is affected by lighting conditions and the distance between the sensor and the object. The test results show that the system built is able to improve transparency, accuracy, and efficiency in cash management at school, while making it easier for students to make cash payments.